Pengaruh Spiritualitas dan Kreatifitas Terhadap Kinerja Guru Akidah Akhlak - Abdul Khanip; Ikhrom Ikhrom (Permata : Jurnal Pendidikan Agama Islam, 2023)
Spirituality is a breakthrough to encourage teacher motivation in increasing the capacity and quality of work. The process of working with spirituality will be able to realize the creativity of teachers in their performance towards quality learning. This study aims to determine the influence between spirituality and teacher creativity on the performance of Akidah Akhlak Madrasah Aliyah teachers in Demak Regency. The research approach used is quantitative research, while the research design used is descriptive with expost facto research type. The research data was obtained using the correlational method by distributing questionnaires to respondents of 165 Akhlak teachers in Madrasah Aliyah in Demak Regency. Based on the results of the questionnaire, teacher spirituality together with teacher creativity affected the performance of Akidah Akhlak teachers in Madrasah Aliyah throughout Demak Regency. From the results of multiple linear regression, it is known that Y = 0.590 x X1 + 0.173 x X2 + 12,012. From the regression line equation above, it can be seen that 0.590 > 0.173 which means that the teacher's spirituality factor which is worth 0.590 is greater than the teacher's creativity value, which is 0.173 so that teacher spirituality is more influential than teacher creativity on teacher performance.Keyword: Teacher Spirituality; Teacher Creativity; Teacher Performance.